Impact of furniture arrangement on sitting movement pattern among pre-and primary school children - Valikhani, Mahkameh (2015)
Pre-schools and primary schools are influential parts with prominent role in life of children. On top of that, at the start of this section of their life, reading and writing would begin. Studies found that there are relationships between school performance and furniture in the classroom. This study found considerable body of researchadd ressing the role of school furniture on children‘s health, performance and seating behavior. The study found how to design the arrangement of furniture in the classroom environment is an important parameter. Scholars confirmed that there is a connection between furniture arrangement and children‘s verbal interaction and cooperation in classroom. However, its impacts on seating behavior and movement pattern have received fairly insufficient attention in literature. Hence, this study was carried out to know the impacts of seating arrangement on children‘s sitting movements and sitting position. For this purpose, a classroom in a governmental primary school was selected. A functional model seating arrangement was designed for testing the hypothesis. With an experimental research design, the study gathered numerical data via passive observation assessment about seating postures. The obtained results demonstrated that appropriate furniture arrangement has critical impact on the way that children sit and move in the classroom.